2017
DOI: 10.1177/0194599816687740
|View full text |Cite
|
Sign up to set email alerts
|

Smartphone‐Enabled Otoscopy in Neurotology/Otology

Abstract: Objective. A smartphone-enabled otoscope (SEO) can capture tympanic membrane (TM) images. We sought to compare a SEO to microscopic otoscopy in the detection and evaluation of TM pathology in an otology/neurotology practice.Study Design. Prospective single-site study in adults presenting over a 3-month period.Setting. Neurotology clinic within a tertiary care academic medical center.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
59
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(60 citation statements)
references
References 15 publications
(24 reference statements)
1
59
0
Order By: Relevance
“…A major benefit of using smartphones is that they can be coupled with other devices allowing otoscopy to be utilized on the same platform. Smartphone‐enabled otoscopes can easily capture images of the ear canal and tympanic membrane and save them to be shared and referenced in the future . Furthermore, other smartphone attachments may facilitate other CHW‐driven screening on the same platform, including vision screening.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A major benefit of using smartphones is that they can be coupled with other devices allowing otoscopy to be utilized on the same platform. Smartphone‐enabled otoscopes can easily capture images of the ear canal and tympanic membrane and save them to be shared and referenced in the future . Furthermore, other smartphone attachments may facilitate other CHW‐driven screening on the same platform, including vision screening.…”
Section: Discussionmentioning
confidence: 99%
“…Programs using calibrated headphones, tablet computers, and smartphones have been clinically validated in collecting accurate audiometric thresholds in pediatric populations . Specialized cameras have also been developed for smartphone applications to provide reliable otoscopic imaging as a proxy for physical examination, which is used for diagnostics and medical decision‐making for hearing loss …”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that pediatricians and otolaryngologists provide an accurate diagnosis of middle ear pathology in only 50% and 73% cases, respectively [17]. Some studies reported a diagnostic accuracy among otologists of 72-82% [18,19].…”
Section: Discussionmentioning
confidence: 99%
“…For this purpose, however, always a special adapter to be fixed to the usual endoscope or otoscope has to be applied. A total of 5 studies could be identified that described the use of smartphones for imaging in otorhinolaryngology [44][45][46][47][48]. Two papers compared the quality of the images with classic procedures.…”
Section: Studies On Apps Referring To Tinnitusmentioning
confidence: 99%
“…Two papers compared the quality of the images with classic procedures. In both studies, a high quality of the app-based imaging could be revealed which fosters the use of smartphones for endoscopic examinations in clinical routine [47,48]. Another publication described the possible application of the devices by non-experts, e. g. parents, for telemedical findings [45].…”
Section: Studies On Apps Referring To Tinnitusmentioning
confidence: 99%